2015
DOI: 10.1890/14-1505.1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological disturbance diminishes predator control in wetlands

Abstract: Effects of predators on prey populations can be especially strong in aquatic ecosystems, but disturbances may mediate the strength of predator limitation and even allow outbreaks of some prey populations. In a two-year study we investigated the numerical responses of crayfish (Procambarus fallax) and small fishes (Poeciliidae and Fundulidae) to a brief hydrological disturbance in replicated freshwater wetlands with an experimental drying and large predatory fish reduction. The experiment and an in situ predati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…by hunting [31]. For example, it was previously observed that the prey population release following the hydrological disturbance in a freshwater ecosystem was due to the reduced abundance of large sized predators [16]. A similar pattern has been also observed in an island ecosystem following a hurricane which reduced the abundance of top predators and caused herbivore outbreak [15].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…by hunting [31]. For example, it was previously observed that the prey population release following the hydrological disturbance in a freshwater ecosystem was due to the reduced abundance of large sized predators [16]. A similar pattern has been also observed in an island ecosystem following a hurricane which reduced the abundance of top predators and caused herbivore outbreak [15].…”
Section: Discussionmentioning
confidence: 67%
“…2b, d). This is a clear sign of prey release [16, 30]. Effectively, disturbance had uncoupled the two interacting species, such that the prey population was no longer relevantly affected by its predator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since crayfish can burrow into the substrate, the crayfish population is not only better equipped than fish to survive periods of drought, but already spread across the landscape once water levels increase (Dorn & Trexler, ; Dorn & Volin, ). As a result, crayfish populations can rapidly increase after severe dry‐downs (Dorn & Cook, ), whereas certain fish species are poor dispersers and may take several years to both recolonise and repopulate areas that have completely dried (Ruetz et al ., ; Goss, Loftus & Trexler, ). However, crayfish populations may be more constrained by predation and food availability (Jordan et al ., ; Kellogg & Dorn, ), both factors that were not represented in our models.…”
Section: Discussionmentioning
confidence: 99%
“…The specific mechanisms through which drought altered the effects of fishes on invertebrate communities could involve several direct and indirect pathways. Although the locations and identities of fish species observed over the sampling period remained consistent (i.e., there was no evidence of local extirpations or colonisations of fish), it is possible that drought‐driven decreases in fish abundance or size distribution could have dampened the intensity of predation risk on sensitive macroinvertebrate taxa (Dorn & Cook, ). Alternatively, evaporation and reduction in pond size are associated with numerous physiochemical changes that can have significant effects on fish behaviour and microhabitat use, such as warmer temperatures, higher salinity and reduced areas of vegetated shoreline (Crowder & Cooper, ; Magoulick & Kobza, ; Webster, Atton, Ward, & Hart, ).…”
Section: Discussionmentioning
confidence: 99%